The Impact of BK Virus and Cytomegalovirus Infections on Graft in Renal Transplant Patients: Experience of a Tertiary Hospital in Turkey - Şükran KÖSE; Sabri ATALAY; Yıldız ULU; Ufuk SÖNMEZ; Süheyla SERİN SENGER (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: BK virus (BKV) and cytomegalovirus (CMV) infections are common in renal transplant patients. In this retrospective study, we investigated the frequency of BKV and CMV infections and their effects on graft. Materials and Methods: The data of 118 renal transplant recipients who were transplanted and followed-up between January 2010 and January 2011 were reviewed. Demographic characteristics, biochemical data, BKV and CMV DNA levels by polymerase chain reaction (QIAGEN, Hilden, Germany) were investigated. The patients were followed-up monthly in the first six months and then every three months. Results: A total of 118 patients were included in the study. BK viraemia was detected in 12 (10.2%) patients and the DNA level of BKV was >104 copies/mL in five cases. Three patients with elevated creatinine and compatible renal biopsy findings were considered to have BKV-associated nephropathy (BKVAN). With the reduction of immunosuppressive treatment, viraemia was reduced and creatinine levels decreased within normal levels. Cytomegalovirus DNA was found to be positive in 23 (19.5%) patients, and was >500 copies/mL in 4 (3.4%) patients. The viraemia in these four patients has decreased after antiviral therapy. No CMV related disease were found in any of the patients. Cytomegalovirus DNA positivity at low levels were also detected in three patients who were diagnosed with BKVAN. None of the patients developed rejection. Conclusion: BK and CMV infections in kidney transplant patients are common and can be seen together. However, graft dysfunction and rejection rates are low with close monitoring, early diagnosis and treatment. Randomized, controlled studies with larger patient groups are necessary in order to determine the viral threshold levels associated with graft dysfunction or rejection, to decide the optimal management and to explain the role of concomitant infection.